Plasticity of Human Protein Disulfide Isomerase: EVIDENCE FOR MOBILITY AROUND THE X-LINKER REGION AND ITS FUNCTIONAL SIGNIFICANCE - Wang, Chao (American Society for Biochemistry and Molecular Biology, 2010)
Protein disulfide isomerase (PDI), which consists of multiple domains arranged as abb′xa′c, is a key enzyme responsible for oxidative folding in the endoplasmic reticulum. In this work we focus on the conformational plasticity of this enzyme. Proteolysis of native human PDI (hPDI) by several proteases consistently targets sites in the C-terminal half of the molecule (x-linker and a′ domain) leaving large fragments in which the N terminus is intact. Fluorescence studies on the W111F/W390F mutant of full-length PDI show that its fluorescence is dominated by Trp-347 in the x-linker which acts as an intrinsic reporter and indicates that this linker can move between “capped” and “uncapped” conformations in which it either occupies or exposes the major ligand binding site on the b′ domain of hPDI. Studies with a range of constructs and mutants using intrinsic fluorescence, collision quenching, and extrinsic probe fluorescence (1-anilino-8-naphthalene sulfonate) show that the presence of the a′ domain in full-length hPDI moderates the ability of the x-linker to generate the capped conformation (compared with shorter fragments) but does not abolish it. Hence, unlike yeast PDI, the major conformational plasticity of full-length hPDI concerns the mobility of the a′ domain “arm” relative to the bb′ “trunk” mediated by the x-linker. The chaperone and enzymatic activities of these constructs and mutants are consistent with the interpretation that the reversible interaction of the x-linker with the ligand binding site mediates access of protein substrates to this site.